Can interactive mind mapping method improve students’ vocabulary mastery? - Yulianti, Fitri (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This research investigates the use of interactive mind mapping method in teaching vocabulary for the secondary school students on SMPN 32 Semarang. The purposes of this research are: (1) to find out the students’ vocabulary achievement before using the interactive mind mapping method; (2) to find out the students’ vocabulary achievement after using the interactive mind mapping method; and (3) to find out the average increasing score between before and after the treatment through interactive mind mapping method. Pre-experimental research was chosen as the research method of this study. Test and questionnaire were the main instruments to collect the data. The population of this study were 285 students who were in the 7 th graders. The sample of this research was the students on 7H with total 31 students. But in the process of taking the data, there were only 24 students who taking part from the beginning to the end of research. The result of this study showed that the average score of students’ vocabulary mastery increased from 81.4 before using mind mapping method to 86.9 after using mind mapping method. The average increasing score was 5.5 (6.36%). It was suggested that (1) the students need to apply interactive mind mapping method on the way they learn vocabulary; (2) the teachers should use interactive mind mapping method in class to improve their students’ vocabulary mastery; and (3) the result of this study can be use as one of the references to whom interested in the same topic.